Extent of Adoption of Castor Production Technology by FLD and Non FLD Farmers in Banaskantha District of Gujarat State - Kakkad, D.M.; Patel, G.R.; Thakur, N.B. (Indian Journal of Extension Education, 2019)
The study was conducted in three talukas (Dantiwada, Vadgam and Dhanera) of Banaskantha District. All the nine villages in which frontline demonstrations on castor crop were conducted by KVK, Deesa were selected and a total of 150 respondents were selected for the study. The result revealed that nearly three-fifth (57.33%) of FLD respondents were in medium randomly category of adoption of castor production technology. Whereas 22.67 per cent had high and 20.00 per cent had low extent of adoption. In case of Non-FLD farmers, majority had medium extent of adoption of castor production technology, whereas, 30.67 per cent had low and 13.33 per cent had high level of adoption.
Keywords: Castor growers; Extent of adoption; FLD; Non-FLD; Castor production technology